2021
DOI: 10.1002/er.6388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oxygen reduction reaction on B doped FeN 4 G and FeN 4 CNT catalysts for proton‐exchange membrane fuel cells

Abstract: Density functional theory (DFT) was used to calculate the stability, oxygen reduction reaction (ORR) mechanism and activity of B-doped FeN 4 CNT (carbon nano-tube [CNT]) and FeN 4 G (G, graphene). The B-doped catalysts are more stable and active than that of the un-doped, especially for FeN 4 B2 G and FeN 4 B2 CNT. Based on the Mulliken charge and electrostatic potential surface of these catalysts, Fe atom is found to be the most active site for the adsorption of O-contained species. It is shown that their ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…To make clear the ORR activity of FeN 4 sites, we further conduct the free energy calculations as shown in Figure 4. It should be noted that, the calculated free energy diagram of FeN 4 in agreement with the free energy diagrams that has been reported in the literatures [34,35] . Under CPS of 1.23 V, the hydrogenation and resolution of OH* become accessible, and the step corresponding to the maximum free‐energy changes (ΔGmax) is the O 2 adsorption for III‐B, IV‐B, and V‐B or O 2 hydrogenation for I‐B and II‐B, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To make clear the ORR activity of FeN 4 sites, we further conduct the free energy calculations as shown in Figure 4. It should be noted that, the calculated free energy diagram of FeN 4 in agreement with the free energy diagrams that has been reported in the literatures [34,35] . Under CPS of 1.23 V, the hydrogenation and resolution of OH* become accessible, and the step corresponding to the maximum free‐energy changes (ΔGmax) is the O 2 adsorption for III‐B, IV‐B, and V‐B or O 2 hydrogenation for I‐B and II‐B, respectively.…”
Section: Resultssupporting
confidence: 89%
“…It should be noted that, the calculated free energy diagram of FeN 4 in agreement with the free energy diagrams that has been reported in the literatures. [34,35] Under CPS of 1.23 V, the hydrogenation and resolution of OH* become accessible, and the step corresponding to the maximum free- An example of the most stable adsorption configurations of the ORR intermediates on the I-B candidate is shown in Figure 5 and the detailed free energies are collected in Table 1 and Table 2. In CPS of 1.23 V, the maximum freeenergy changes (ΔG max ) of FeN 4 sites is 0.55 eV, and most candidates of B-doped FeN 4 /C exhibit superior ORR catalytic activity (ΔG max below 0.55 eV) compared to FeN 4 /C, except for II-B which has a similar ORR activity (0.62 eV) to undoped FeN 4 sites.…”
Section: Structure and Stability Of B-doped Fenmentioning
confidence: 99%
“…Similar to P atoms, B atom doping is also a feasible strategy to adjust the electronic structures of M-N-C SACs. [126][127][128][129] Recently, Sun et al reported a B-doped Fe-N 4 catalyst with Fe single atoms anchoring on B, N-doped carbon nanotubes (Fe SA /B,N-CNT, see Fig. 5a-c).…”
Section: Environment Engineering For M-n-c Sacsmentioning
confidence: 99%
“…40,41 It is worth mentioning that the CNT-based SAC systems have been used as effective electrocatalysts for both the HER [42][43][44] and ORR. [45][46][47][48] However, relevant research is quite scarce, especially on the OER electrocatalytic activity of SACs based on CNTs.…”
Section: Introductionmentioning
confidence: 99%